2020
DOI: 10.1016/j.ejwf.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of the COVID-19 pandemic on orthodontic practice by orthodontists and orthodontic residents in Nigeria

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has had far-reaching effects on orthodontic care delivery worldwide. This study aimed to assess the impacts of the pandemic on orthodontists and orthodontic residents in Nigeria. Methods This cross-sectional study was conducted among consenting orthodontists and orthodontic residents. The respondents were contacted through the WhatsApp group of the Nigerian Association of Orthodontists to fill the self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 12 publications
6
32
1
Order By: Relevance
“…1 Orthodontists share a similar perception; as a study on the impact of COVID-19 among Nigerian orthodontists showed that the majority of them considered the infection dangerous. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Orthodontists share a similar perception; as a study on the impact of COVID-19 among Nigerian orthodontists showed that the majority of them considered the infection dangerous. 14 …”
Section: Discussionmentioning
confidence: 99%
“…1 Orthodontists share a similar perception; as a study on the impact of COVID-19 among Nigerian orthodontists showed that the majority of them considered the infection dangerous. 14 Most of the participants had not visited the orthodontic clinic since the onset of the pandemic. This result is contrary to the findings of Peloso et al, 19 who reported that more than 50% of Brazilian patients attended the dental clinic, predominantly for orthodontic procedures since the pandemic began.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coronavirus Disease 2019 (COVID- 19) pandemic has had profound effects on orthodontic care delivery worldwide. 4 Considering the generation of copious amounts of droplets along with the aerosols formed during routine dental procedures, the conventional protective measures routinely followed by dental clinicians are unfortunately no longer efficient for prevention of COVID-19 transmission. 5 According to a report by the New York Times, dental clinicians have the highest risk of exposure, even higher than that of nurses, physicians and pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore essential that all practitioners adapt their practices to new recommendations to protect themselves and patients until a vaccine is developed [21]. A study from Nigeria found that most Nigerian orthodontists and orthodontic residents responded that because of COVID-19, they would change their future practice of orthodontics, particularly with respect to placing a greater emphasis on infection control [22].…”
Section: Introductionmentioning
confidence: 99%